Tinjauan Yuridis Perlindungan Hukum Terhadap Anak Akibat Perkawinan Siri (Studi Putusan Nomor: 129/Pdt.G/2018/PN. Lbp) - Syarifuddin, Syarifuddin; Faisal, Muhammad (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
Marriage aims to form a sakinah, mawaddah, warahmah family, and to create order in the society and the legal certainty for husbands, wives and descendants. The decision of the Class IA Lubuk Pakam District Court, Number: 129/Pdt.G/2018/PN Lbp, has examined and decided on divorce claims that were not registered with the competent authorities, even making KHI as part of the legal considerations in terms of child custody, this is strictly a statutory provision, based on this the author discusses the legal arrangements for unregistered marriages, legal consequences, and the protection of women and children based on the Decision Number: 129/Pdt.G/2018/PN Lbp.The legal arrangements regarding the protection of children from unregistered marriages are regulated in the Articles 21 and 27 in conjunction with the Article 39 of the PA Law; children must get legal protection from parents and the government. The legal consequences of unregistered marriages have a negative impact on women and children, because their rights and legal status are not recognized by the state, this shows that women and children are the most disadvantaged due to unregistered marriages. The judge's legal considerations are very wrong and irrelevant, because unregistered marriages are legal even though they are not registered with the authorized official, so that the basis for the lawsuit is filed without a marriage book and child's birth certificate. Furthermore, the judge's consideration in child custody uses KHI in the consideration of child custody for the divorce cases for non-Muslim communities.Keywords: Legal Protection, Women and Children, Unregistered Marriage.